2023
DOI: 10.1093/mnras/stad177
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of the lump in circumbinary discs

Abstract: Accreting binary black holes (BBHs) are multi-messenger sources, emitting copious electromagnetic (EM) and gravitational waves. One of their most promising EM signatures is the lightcurve modulation caused by a strong, unique and extended azimuthal overdensity structure orbiting at the inner edge of the circumbinary disc (CBD), dubbed ‘lump’. In this paper, we investigate the origin of this structure using 2D general-relativistic (GR) hydrodynamical simulations of a CBD in an approximate BBH spacetime. First, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Although we focused on stellar-mass BHs for being typical XMM sources, our results can be scaled to SMBBHs (Mignon-Risse et al, 2022). An increase in BBH mass would reduce the emission frequency and increase the period of the signal, hence the variability coming from a stellar-mass BBH is widely different from a SMBBH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we focused on stellar-mass BHs for being typical XMM sources, our results can be scaled to SMBBHs (Mignon-Risse et al, 2022). An increase in BBH mass would reduce the emission frequency and increase the period of the signal, hence the variability coming from a stellar-mass BBH is widely different from a SMBBH.…”
Section: Discussionmentioning
confidence: 99%
“…In case of a gas-rich environment around the stellar-mass BBH, a circumbinary disk is expected to form (from angular momentum conservation). In this paper, we study how the circumbinary disk behaves in the radiation zone where GWs will propagate and retardation effects become important (see Mignon-Risse, Varniere, & Casse 2022), that we will refer to as radiation zone effects for conciseness, looking for its spectro-timing properties as seen by a distant observer. An EM signal directly related to the radiation zone effects would point, unequivocally, to a BBH system rather than a single BH with the same mass and disk.…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that such features might arise from a Rossby wave instability (RWI; Lovelace et al 1999) or a generalized form of the Papaloizou-Pringle Instability (PPI; Papaloizou & Pringle 1984). The presence of the RWI within disks has already been argued in the case of tidal disruption events (TDEs) and the spirals it produces may explain the observed flaring behaviors in Sgr A * (Falanga et al 2007;Mignon-Risse et al 2021). A similar feature was also reported in an MHD simulation by Mishra et al (2020), who observed spiral-like inhomogeneities in the density of disks with initially weak poloidal fields; however, these simulations were only run for 23 orbits (versus our ∼6500 for b200) and so the late-time evolution of the effect was not noted.…”
Section: Evolution Of the Disk Structurementioning
confidence: 97%
“…In this work, we build on the simulations presented in the companion paper (Mignon-Risse et al 2022a), that we refer to for more details, in which we address the electromagnetic observables associated to pre-merger BBHs. Those 2D inviscid general-relativistic hydrodynamical simulations were performed with the latest version of the GRMHD code GR-AMRVAC (Casse et al 2017) recently extended to any kind of spacetime metric (Mignon-Risse et al 2022b) and based on MPI-AMRVAC (Keppens et al 2012). The gravitational influence of the orbiting BBH is taken into account via an approximate analytical spacetime construction, sometimes referred to as "Near Zone" metric (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, 𝛿 𝑗 𝑖 is Kronecker's symbol. More details on the implementation of the code can be found in Mignon-Risse et al 2022b. In this frame, we will study the evolution of a circumbinary disc orbiting the BBH, addressing the equal-mass and unequal-mass cases, focusing on the symmetry breaking and lump formation.…”
Section: Introductionmentioning
confidence: 99%